Análisis e interpretación de los estados financieros y su importancia en la toma de decisiones. Caso BBVA Continental, periodo 2015 – 2017 - Manrique Dobashi, Raúl Eduardo (2018)
The bank BBVA Continental began its activities on October 9 of 1951 and it is dedicated to the Multiple banking (people banking, corporate banking, institutional banking and corporate banking). Regarding its participation in the market, the BBVA Continental bank has S / 51,932 million (21% of direct loans from multiple banks) of direct loans issued in multiple banks and S / 48,646 million, which represents 21% of the multiple banking deposits. The objective of this paper is analyze the financial information based on the Audited Financial Statements of BBVA Continental bank for the culminated periods of 2015-2017. To complement this research information was gathered from different sources such as: information from web pages (BVL, SBS, among others). Likewise, the financial situation with the financial ratios were analyzed and then the financial statements were projected.